Melacak Minat Siswa SMP Negeri 2 Kismantoro dalam Melanjutkan Pendidikan - Purwanta; Anirotun Nisa; Reni Ramadhina; Lestari; Ahmad Sidik Pramono; Defa Rizky Pratama; Christy Paramitha; Muhammad Fakhrizal (Direktorat Pengabdian kepada Masyarakat, 2024)
Several factors influence a child's interest in pursuing higher education, including their awareness of their own potential. Unfortunately, many students are unaware of their abilities, which affects their motivation in making further education choices. Limited information and the distance to schools can also impact the decisions of students at SMP Negeri 2 Kismantoro in continuing their education. This research was conducted as part of the UGM SCS-CEL program Period 2 of 2023 in Kismantoro District, Wonogiri Regency. The study aimed to explore the factors influencing students' motivation to continue their education to a higher level. The research process was divided into two stages: the pre-consultation assessment stage and the consultation stage. The data analysis method used was qualitative descriptiveanalysis. Based on the consultation with 21 students in grade IX of SMP Negeri Kismantoro, several reasons were revealed on why students did not continue their education. Major factors included mobilization constraints, particularly for students whose schools are far away and who lack private transportation. In addition, most students had not yet realized their potential. As a result, schools are encouraged to help students recognize their potential through interest and aptitude tests, as well as guidance and counseling. The assessments and consultations conducted can provide input for schools to address the problem of student dropouts. Furthermore, assistance from other parties is necessary to ensure the continuity of this program.